Kajian Lafaz dalam Teks Hukum Islam: Analisis Dalālat Al-Manṭūq dan Implikasinya terhadap Istinbāṭ Al-Ḥukm - Nurmilasari; Abd. Rauf Muhammad Amin; Fatmawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The analysis of wording (lafaz) in Islamic legal texts occupies a central position in the methodology of Islamic jurisprudence, particularly in the process of legal derivation (istinbāṭ al-ḥukm). Explicit textual meaning (dalālat al-manṭūq) represents the most direct form of legal indication and functions as a primary reference before engaging implicit meanings or analogical reasoning. However, contemporary legal discussions often reveal inconsistencies in understanding the scope and authority of explicit meaning, leading to divergent legal conclusions. This article examines the forms and classifications of dalālat al-manṭūq and analyzes their implications for legal reasoning within the framework of uṣūl al-fiqh. Employing a qualitative descriptive-analytical approach, the discussion is grounded in a critical review of classical and contemporary uṣūl al-fiqh literature. The findings demonstrate that dalālat al-manṭūq al-ṣarīḥ holds strong legal authority due to its clarity and minimal interpretative ambiguity, while dalālat al-manṭūq ghayr al-ṣarīḥ, although still authoritative, requires careful contextual and linguistic analysis. The study highlights the continuing relevance of precise textual interpretation in responding to modern legal challenges and emphasizes that methodological rigor in understanding explicit meaning is essential to ensure legal rulings remain aligned with the objectives of Islamic law (maqāṣid al-sharīʿah).